Status and Trend of R&D Disclosures: A Study of Selected Organizations in India - Dhawan, Neha; Dharni, Khushdeep (Indian Journal of Finance, 2014)
The present study was undertaken to explore the R&D activities of selected companies in India. An attempt has been made to find out variations relating to R&D activities among various sectors and companies. R&D activities for the purpose of this study included the amount of R&D expenditure as well as other R&D disclosures made in the annual reports of the companies. Content analysis was used for measuring qualitative disclosures. Five companies each from five sectors, namely, biotechnology, pharmaceuticals, information technology (IT), food, and fertilizers, with the period of analysis covering 10 years from 2002-03 to 2011-12, were included in the study. Results indicate that pharmaceuticals and biotechnology are the leading sectors for R&D intensity in India. Overall, a positive growth was observed for R&D activities across the board. Significant positive correlation was found between R&D expenditure and qualitative R&D disclosures.